Prognostic value of the white blood cell-to-hemoglobin ratio (WBC/Hb) for inhospital mortality: Insights from a retrospective cohort study in Uganda - Changhui Wu; Kuule Julius Kabbali; Kamugisha Richard; John Wanyama; Gemagaine Godfrey; Odong Christopher (PLoS ONE, 2026)
Background The white blood cell-to-hemoglobin ratio(WBC/Hb), composite marker derived from routine laboratory parameters, may offer unique prognostic value by integrating systemic inflammation and physiological reserve. This study investigates its association with inhospital mortality(IHM) in a resource-limited medical setting. Methods We retrospectively enrolled patients admitted to medical ward of Naguru regional referral Hospital-Uganda, between January and June 2024. Data on demographics, clinical status, and lab results, including WBC-count and hemoglobin, were extracted on admission. The primary outcome was IHM. Patients were categorized into three WBC/Hb subgroups. Hazard ratios(HR) and Area Under the Curve(AUC) assessed its prognostic value, adjusting fully for age, sex, comorbidities, and admission diagnoses. Results Overall, 226 patients were included(mean age 45.35 ± 18.85yrs, 54.4% female). The mean WBC/Hb ratio was 1.04 ± 1.22 × 10⁹ cells/L per g/dL, and IHM rate was 19.9%. Per-standard increase of WBC/Hb(2.22 × 10⁹ cells/L per g/dL) was associated with high-risk of IHM (HR 1.19, 95% CI 1.00–1.44; p = 0.012). The Results were similar when stratified into three groups (<0.55, 0.55–1.00, and ≥1.00 × 10⁹ cells/L per g/dL), compared with the reference group(<0.55), 0.55–1.00 group (HR 2.81, 95% CI 1.06–7.43; p = 0.037) and ≥1.00 group (HR 2.82, 95% CI 1.05–7.57; p = 0.040) had significantly high-risks of IHM. WBC/Hb demonstrated predictive value for IHM with AUC of 0.701 (95% CI 0.550–0.718). Conclusion WBC/Hb, readily available and cost-effective marker, was associated with IHM. Incorporated into routine clinical assessments could improve risk stratification, especially in resource-limited settings. Prospective studies are needed to validate these findings and assess its broader utility.